Cost-benefit analysis Canavalia brasiliensis hay supplementation in Colombian dual-purpose cattle systems - Junca Paredes, Jhon Jairo; Jauregui, Rosa; Mojica Rodríguez, José Edwin; Sotelo, Mauricio E.; Burkart, Stefan (International Center for Tropical Agriculture, 2023)
Context: In the Colombian Caribbean region, small-scale livestock farming systems are characterized by relying on Bothriochloa pertusa (Colosuana) grass for grazing, often with minimal land improvement investments. While Colosuana yields satisfactory results, its productivity and quality decline during the dry season. To address this challenge, supplementing animal diets with legumes have proven effective, with Canavalia brasiliensis demonstrating promising outcomes in the region.